Examining the students' behavioral intention to use e-learning in Azerbaijan? The General Extended Technology Acceptance Model for E-learning approach. (August 2017) - Chang, Ching-Ter; Hajiyev, Jeyhun; Su, Chia-Rong
Abstract: Azerbaijan has successfully incorporated modern Information Communication Technologies (ICT) in the education system. The major goal is to raise the standard of education. The factors that affect university students' behavioral intention (BI) to use e-learning for educational purposes in Azerbaijan are worthy of study. This is an empirical study of the use of the General Extended Technology Acceptance Model for E-learning (GETAMEL) developed by Abdullah and Ward (2016) in order to determine the factors that affect undergraduate students' BI to use an e-learning system. The data was collected from 714 undergraduate and masters students using a convenient sampling technique and the responses were analyzed using Structural Equation Modeling (SEM). It is seen that the Subjective norm (SN), Experience (EXP) and Enjoyment (ENJOY) positively and significantly influence students' perceived usefulness (PU) of e-learning, while Computer anxiety (CA) has a negatively effect. EXP, ENJOY and Self-efficacy (SE) positively and significantly affect their perceived ease of use (PEOU) of e-learning. It is also seen that SN has a positive and significant impact on BI to use e-learning, while Technological innovation (TI) significantly moderates the relationship between SN and PU, PU and BI to use e-learning. This study is the first to determine a negative and significant relationship between CA and PU, in the context of students' e-learning. This study is also one of the very few that uses the GETAMEL model for e-learning settings. The results have significant practical implications for educational institutions and decision-makers, in terms of the design of the e-learning system in universities. Graphical abstract: Highlights: The GETAMEL model successfully applies to e-learning acceptance domain. Computer anxiety negatively affects perceived usefulness and perceived ease of use. Subjective norm does not have an impact on perceived ease of use of e-learning system. Self-efficacy does not affect perceived usefulness of e-learning system. perceived ease of use does not affect perceived usefulness of e-learning system.